Comparison of Donor Corneal Endothelial Cell Density Determined by Eye Banks and by a Central Image Analysis Reading Center Using the Same Image Analysis Method. Issue 5 (23rd May 2022) - Huang, Heidi; Benetz, Beth Ann; Clover, Jameson M.; Titus, Michael; O'Brien, Robert C.; Menegay, Harry J.; Lass, Jonathan H.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to evaluate agreement between eye banks (EBs) and an image analysis reading center on endothelial cell density (ECD) determinations using the same image analysis method. Methods: The Cornea Image Analysis Reading Center (CIARC) determined ECD with a single experienced analyst on EB-obtained central endothelial images from donors intended for keratoplasty from 2 eye banks, Eversight and Lions VisionGift, using the Konan center analysis method. The EBs performed ECD determination on their respective sets of images using the same analysis method with experienced eye bank technicians. Results: The mean age of the 200 donors was 54 years (range 30–75 years). Seventy (35%) of the 200 patients were women, and 57 (29%) were diabetic. The mean ECD was 10 cells/mm 2 greater by the EBs than by CIARC ( P = 0.39), with 95% limits of agreement of [−304 to 323 cells/mm 2 ]. The mean difference was not substantially changed when the difference between EBs and CIARC ECD was adjusted for sex, donor age, donor diabetes, CV, HEX, number of cells analyzed, and EBs as a random effect (estimated mean difference of 20 cells/mm 2 after adjustment in a linear mixed model; P = 0.73). The EB-determined preoperative ECD was within 10% of the CIARC-determined ECD for 178 (89%) image sets, with 15 (8%) higher by >10% and 7 (3%) lower by >10%. Conclusions: Well-trained eye bank technicians achieve comparable results for ECD determination with an experienced image analyst from an image analysis reading center when the same image analysis method is used.